Повести. Рассказы - Искандер Фазиль Абдулович (Советская Россия, 1989)
Экземпляры: Ф. 13 (20200221) / Инвентарный номер: 47633 / Цена: 6.57 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: И 86 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44